Chiral Framework with 20‐Ring Channels Exhibiting Metal‐Activator‐Free Photoluminescence. Issue 19 (7th April 2014) - Huang, Hui‐Lin; Luo, Zih‐Jie; Kuo, Yu‐Chih; Wang, Sue‐Lein
Abstract The use of biomass‐derived sucrose has unprecedentedly induced the first chiral zinc phosphite structure with 20R channels along with a series of acentric frameworks, unveiling a facile synthesis of chiral nanoporous frameworks. The 20R‐channel structures are metal‐activator free but display blue‐to‐white photoluminescence under long UV excitation.